Characterization of Lasiodiplodia species associated with grapevines in Mexico - Rangel Montoya, Edelweiss A. (2021)
Botryosphaeria dieback is one of the most prevalent grapevine trunk diseases (GTDs), and is caused by fungi in the Botryosphaeriaceae. Fungi invade grapevine vascular systems mainly through pruning wounds, and cause cankers and necrotic lesions, which lead to grapevine decline and death. Lasiodiplodia theobromae has been reported as a highly virulent pathogen of grapevine, and was previously reported in Mexican vineyards. The taxonomy of Lasiodiplodia was recently revised, adding new species, and some were reduced to synonymy. This study aimed to characterize Lasiodiplodia producing grapevine dieback symptoms in Sonora and Baja California, Mexico. Using the phylogenetic markers tef1-α and ITS regions, Lasiodiplodia brasiliensis, L. crassispora, L. exigua, and L. gilanensis were identified. Lasidiplodia exigua was the most prevalent species. Lasiodiplodia brasiliensis and L. gilanensis were very virulent to ‘Cabernet Sauvignon’ plants, while L. exigua and L. gilanensis were less virulent, and L. crassispora did not produce lesions at 2 months post-inoculation. The optimum temperature of the Lasiodiplodia spp. was 28°C, but all four species grew up to 37°C, and the isolates of L. exigua grew slowly at 40°C. This is the first report of the four of Lasiodiplodia species in vineyards of Mexico.